2018
DOI: 10.1523/jneurosci.1931-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced Hyperactivity, Cognitive Dysfunctions, and BDNF Dysregulation in Dopamine Transporter Knock-out Rats

Abstract: Dopamine (DA) controls many vital physiological functions and is critically involved in several neuropsychiatric disorders such as schizophrenia and attention deficit hyperactivity disorder. The major function of the plasma membrane dopamine transporter (DAT) is the rapid uptake of released DA into presynaptic nerve terminals leading to control of both the extracellular levels of DA and the intracellular stores of DA. Here, we present a newly developed strain of rats in which the gene encoding DAT knockout Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
209
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 163 publications
(280 citation statements)
references
References 86 publications
(38 reference statements)
23
209
0
10
Order By: Relevance
“…This difference can be ascribed to different maturation of central nervous system since, during the transition from preadolescence to adulthood, the limbic system and PFC mature differentially. While adolescent behavior typically shows less habituation, due to innate curiosity and age‐related hyperactivity, DAT‐KO adolescents paradoxically exhibited less restless arousal, consistently with calming effects of psychostimulants …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This difference can be ascribed to different maturation of central nervous system since, during the transition from preadolescence to adulthood, the limbic system and PFC mature differentially. While adolescent behavior typically shows less habituation, due to innate curiosity and age‐related hyperactivity, DAT‐KO adolescents paradoxically exhibited less restless arousal, consistently with calming effects of psychostimulants …”
Section: Discussionmentioning
confidence: 99%
“…However, generally rats remain a most preferable model in behavioral neuroscience due to their more developed cognitive skills, allowing operant testing as it was performed on other ADHD rat models like SHR and NHE rats. 40 Just recently DAT-KO rats were developed (see 12 ), however, to be validated as a promising model for ADHD, they should be tested for hyperactivity, altered attentional skills and potential deficits in executive functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to potential TAAR1-mediated regulation of DAT, it should be noted that in other studies, no difference in dopamine uptake rate was observed in either the nucleus accumbens or striatum of TAAR1-KO mice or after TAAR1 agonist/ antagonist treatment of wild-type animals . Furthermore, the partial TAAR1 agonist RO5203648 prevents cocaine-induced dopamine overflow in the nucleus accumbens without altering dopamine uptake (Pei et al, 2014), and TAAR1 agonists are effective in inhibiting dopamine-dependent hyperactivity in DAT-KO mice (Revel et al, 2011(Revel et al, , 2012bLeo et al, 2018) and when DAT has been inhibited by administration of cocaine (Revel et al, 2013). As such, it now appears unlikely that TAAR1-mediated effects occur after a regulation of DAT function.…”
Section: Ro3648 Ro6390 Ro3397mentioning
confidence: 99%